Synbindin deficiency inhibits colon carcinogenesis by attenuating Wnt cascade and balancing gut microbiome. Issue 1 (10th January 2019) - Ai, Luoyan; Ren, Yimeng; Li, Yiting; Chen, Haoyan; Qian, Yun; Lu, Shiyuan; Xu, Antao; Ren, Linlin; Zhao, Shuliang; Chen, Zhaofei; Chen, Ying‐Xuan; Xu, Jie; et al.
Abstract : The molecular mechanisms that control the development of colorectal cancer (CRC) remain poorly defined. Here we show Synbindin promoted CRC oncogenesis by activating Wnt signaling and altering gut microbiome. Synbindin upregulation in human CRCs was associated with poor patient prognosis. Intestine‐specific disruption of Synbindin balanced the disturbed gut microbiota and protected mice against tumor formation in the colitis‐associated cancer (CAC) model. The protective role was compromised after gut microbiota depletion. In host, increased goblet cells and mucin2 expression, together with increased intestinal epithelial cells (IECs) apoptosis and decreased epithelial proliferation were observed. Further transcriptomic sequencing identified Wnt signaling a major regulatory node downstream of Synbindin. Combined molecular and cellular characterizations revealed that Synbindin confers Disheveled‐3 (DVL3)‐based signalosome assembly and acts as a modular scaffold for DVL3 and Axin2 complex, orchestrating the intensity of Wnt signaling. These findings identify a critical role of Synbindin in gut microbiome composition and Wnt signaling activation in colorectal carcinogenesis, and highlight Synbindin as an adaptor protein with multifaceted roles. Abstract : What's new? The molecular mechanisms that control the development of colorectal cancer (CRC) remain poorly defined. This study reveals that Synbindin, which is a major player in vesicular trafficking, plays a critical role in gut microbiome composition and Wnt signaling activation in colorectal carcinogenesis. Synbindin ablation altered the gut microbiome to a more balanced enterotype and protected mice against tumor formation in the colitis‐associated cancer model. In host, Synbindin may act as a novel assembler for DVL3‐based signalosome and help to recruit Axin2, orchestrating the intensity of Wnt signaling. Synbindin thus emerges as a potential clinical marker and therapeutic target for CRC.